PERLINDUNGAN HUKUM ATAS KRIMINALISASI TERHADAP EMIRITUS NOTARIS YANG MEMEGANG DOKUMEN DILUAR PROTOKOL NOTARIS - Ardheva Khalish Adiwena; Mohamad Fajri Mekka Putra (LPSDI Bina Patria, 2025)
This study discusses legal protection for emeritus notaries who face potential criminalization due to holding documents outside the notary protokol. In practice, emeritus notaries often still keep or manage documents related to their past duties, even though they formally no longer have the authority as public officials. This can create legal loopholes that have the potential to be misinterpreted as unlawful acts. Through a normative legal approach and analysis of applicable laws and regulations, this study aims to identify the form of legal protection that can be given to emeritus notaries, as well as to evaluate the limits of their legal responsibilities. The results of the study indicate that legal protection for emeritus notaries needs to be strengthened with clear regulations, in order to avoid detrimental legal interpretations and ensure legal certainty for notaries after their term of office ends.